Formation of human articular cartilage from in vitro to in vivo short-term ectopic implantation model: Gross observation, histology and immunohistochemistry analysis - Sha'ban, Munirah; Mohamad Sukri, Norhamiza; Ahmad Radzi, Muhammad Aa’zamuddin; Abdul Rahman, Rozlin; Mohamad, Mohd Yusof; Md Nazir, Noorhidayah; Zulkifly, Ahmad Hafiz; Hashi, Abdurezak Abdulahi (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
This study aimed to explore the formation of hyaline-like articular cartilage substitute using primary cells derived from osteoarthritic patients overexpressed with SRY(Sex Determining Region Y)-Box9 (SOX9)geneseeded on poly(lactic-co-glycolic acid) (PLGA) with or without fibrin as cells carrier through in-vitro and in vivo experiment settings using the ectopic implantation model i.e. athymic mice. Based on the approved research protocol, the TECs were formed and cultured for three weeks in vitro. The TECs were then implanted subcutaneously at the dorsum of athymic mice for four weeks. All TECs were subjected to gross inspection, histology, and immunohistochemistry (IHC) evaluation. Macroscopically, all in vitro TECs exhibited smooth, white and glossy hyaline-like cartilage appearance. After implantation, the 2-week TECs showed a favourable hyaline-like cartilage appearance when compared to the 4-week TECs. Histologically, all in vitro TECs exhibited minimally or lack cartilaginous tissue formation. The presence of high density, lacunae-encapsulated chondrocytes, distributed in cartilaginous matrices was observed in most postimplanted TECs. Coupled with positive immunoreaction against collagen type II (the cartilage-specific marker), cartilaginous properties were noticeable more in the 2-week than the 4-week post-implanted TECs.